Automatic controlled and monitoring drainage system using CX-Programmer and Touchwin Xinje Designer - Muda, Ahmad Syazani (2020)
This writing present the Intelligent Automatic Drainage Monitoring and Control system which relies on Programmable Logic Controller (PLC). This system is proposed to overcome real time problem. The concept is replace the manual work of drainage gate system by automated system. With the continued expansion of industries and global warming that cause unexpected rainstorm or flash flood, the increasing problem of drainage system must be urgently resolve. PLC is the major controlling unit and the drainage level is monitored by the sensor used. For the Intelligent Automatic Drainage System, level sensor is used to monitor the drainage water level an de motor (24V) as the actuator for the gate system. The software that is used in this project is Touchwin Xinje Designer and OMRON CX-Programmer controlling the automatic drainage system and the touch win as the HMI. CXProgrammer and the Touchwin Xinje Designer are need to be integrated and linked with each other to develop sophisticated and user friendly system. Ladder diagram used as the language to control the whole system.